TOURISM POTENTIAL OF THE COUNTRIES OF THE SHANGHAI COOPERATION ORGANIZATION AND PROSPECTS OF MULTILATERAL COOPERATION (Web of Teachers: Inderscience Research, 2026)
The given article considers the changes, occurring recently in the tourism industry of the countries of the Shanghai Cooperation Organization and focuses on its increasingly increased interdependences with the countries of the Shanghai Cooperation Organization (SCO). There, the attempts at intensifying collaboration in the sphere of tourism are analyzed and in the study the situation with visitor relations between the SCO member states, the development of joint tours, facilitation of the visa policy, and the prospects of increasing infrastructural facilities are discussed. Besides, in the article the special attention is devoted to the active involvement of SCO member states in the form of Russia, Kazakhstan, Kyrgyzstan, Tajikistan, and Uzbekistan; specifically, their efforts in the context of the organization in tourism development, implementation of digital services, and promotion of sustainable tourism concepts are examined. Actual suggestions of sustainable economic growth and development of cultural tourism are provided in the article, in other words, such recommendations as the introduction of effective cheap airline tickets and visa-free travel are offered. Overall, the enlarging tourist industry, and the strategic attempts at forming multifaceted partnership in the SCO area, are narrated to the letter.